POTATO YIELD PRODUCTIVITY BASED ON CALCULATED MINERAL FERTILIZER NORMS FOR THE TARGET YIELD ON DARK GREY PODZOLIC SOIL IN THE WESTERN FOREST-STEPPE REGION OF UKRAINE - Parkhuts , Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
This paper presents research findings on the impact of mineral fertilizers, applied in conjunction with an organic background, on the target yields of 30, 35, and 40 t/ha for the Connect potato variety cultivated in the dark grey podzolic soil of the Western Forest-Steppe region of Ukraine. Prior to the experiment, the levels of mobile forms of key mineral nutrients in the arable layer of the dark grey podzolic soil were measured as follows: easily hydrolyzed nitrogen (determined using the Kornfield method) was found to be 142 mg, mobile phosphorus measured 75 mg, and exchangeable potassium (assessed by the Chirikov method) was 98 mg per 1 kg of soil. The following variants were included in the scheme of the experiment: control – without fertilisers; background (40 t/ha of manure) + the recommended rate for this zone N90P90K120; background + calculated fertiliser rate N53P25K59 for a target yield of 30 t/ha; background + calculated rate of fertiliser N53P58K123 + N50 (applied as topdressing at BBCH 35-37) for a target yield of 35 t/ha; background + calculated rate of fertiliser N53P92K187 + N50 (applied as topdressing at BBCH 35-37) + N50 (applied as topdressing at BBCH 50-52) for a programmed yield of 40 t/ha. The following coefficients were used for the calculations: nutrient use efficiency from soil – N – 0.23, P₂O₅ – 0.10, K₂O – 0.37; nutrient use efficiency from mineral fertilisers – N – 0.60, P₂O₅ – 0.30, K₂O – 0.70; nutrient use efficiency from organic fertilisers – N – 0.25, P₂O₅ – 0.30, K₂O – 0.50. The highest yield of 39.7 t/ha with a target yield of 40.0 t/ha, on average over the years of research, was obtained by applying the calculated mineral fertilisers at the rate of N153P92K187 on a background of 40 t/ha of manure. The yield increase in this variant was 19.9 t/ha, or 100.5 %, and 6.5 t/ha to the recommended rate of background + N90P90K120. The recommended rate of N90P90K120 on the basis of 40 t/ha of manure provided a yield of 33.2 t/ha with an increase of 13.4 t/ha, or 67.7 %, to the control. The lowest potato yield of 19.8 t/ha was obtained in the control variant of the experiment – without fertilisation. The highest starch content of 17.2 % was obtained in the control variant of the experiment, and its total yield of 5.6 t/ha was obtained by applying the calculated rate of mineral fertiliser N153P92K187 on the background of 40 t/ha of manure for a target yield of 40 t/ha. In other variants, the starch yield was slightly lower, and in the control variant it was the lowest and amounted to 3.4 t/ha. The highest net profit of 235100 UAH/ha and a profitability level of 83.5 % were obtained by applying the calculated rate of mineral fertilisers N153P92K187 on a background of 40 t/ha of manure.